PENGARUH STRES PSIKOLOGIS TERHADAP KADAR KORTISOL ASI PADA IBU MENYUSUI DI KABUPATEN SELUMA - Rosaria, Rini Rosaria; Flora, Rostika; Zulkarnain, Mohammad; Sitorus, Rico Januar; Hasyim, Hamzah; Fajar, Nur Alam; Ermi, Nurmalia; Jasmine, Annisah Biancika; Aguscik, Aguscik; Ikhsan, Ikhsan; Slamet, Samwilson; Purnama, Yetti; Sulung, Neshy (LPPM STIKES BHAKTI HUSADA BENGKULU, 2023)
Breast milk is the gold standard in infant nutrition, which is the best food for babies compared to formula milk. Apart from containing the necessary nutrients, breast milk also contains various bioactive compounds that can affect the growth and development of the baby. Among these bioactive compounds there is also a glucocorticoid (GC) content, such as cortisol. It is known that cortisol levels are affected by the level of stress experienced by mothers during pregnancy and after childbirth. Purpose: this study aims to analyze the effect of maternal stress on breast milk cortisol levels in breastfeeding mothers in Seluma District. Method : : This research is an analytic survey, cross sectional study, conducted in Seluma Regency. A total of 77 rbreastfeeding mothers of children aged 0-24 months were taken as respondents by random sampling. Breast milk samples were taken to examine breast milk cortisol levels and were measured using the ELISA method. interviews using a questionnaire were conducted to collect data on maternal characteristics, while the stress level data were obtained by conducting interviews using the DASS 42 questionnaire. The data obtained was then processed and analyzed using univariate and bivariate analysis. Results: The results of measuring psychological stress showed that 35.1% of mothers experienced stress, while the results of measuring breast milk cortisol levels showed that 50% of mothers had high cortisol levels. The results of the Mann Whitney test found that there was a significant difference in the average breast milk cortisol levels in mothers who experienced psychological stress and those who did not (201.65 ± 97.82 μ/mL vs 150.32 ± 81.80 μ/mL, p=0.028) . Conclusion: psychological stress affects breast milk cortisol levels in breastfeeding mothers in Seluma Regency. Education related to handling stress in breastfeeding mothers needs to be done so that it does not hinder the breastfeeding process which can have an impact on the health of mothers and children. Keywords: Breastfeeding mothers, breast milk cortisol level, psychological stress